Literature Review : Analisis Persepsi Peserta Didik Terhadap Penggunaan Media LKPD Biologi : (Literature Review: Analysis of Students' Perception Towards The Use of Biology LKPD Media) - Azzahra, Annisa; Fuadiyah, Sa’diatul (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2024)
This study aims to review scientific journals in order to collect relevant sources related to students' perceptions of LKPD media. The importance of measuring perception is to provide an understanding of how people see, understand, and respond to a situation and help identify differences in individual views and assessments. The method used in writing this article is a literature review. This study began by looking for references in the form of articles related to the research topic to be carried out. The criteria for scientific articles used as data are in the form of scientific articles sourced from journals with an update of the last 10 years, namely from 2012-2022. The results of the analysis of 3 journal articles discussing students' perceptions of LKPD media. There are not many articles that describe students' perceptions of the use of LKPD media. Abstrak. Penelitian ini bertujuan untuk mengkaji jurnal-jurnal ilmiah dalam rangka pengumpulan sumber-sumber yang relevan yang berkaitan dengan persepsi peserta didik terhadap media LKPD. Pentingnya mengukur persepsi ialah untuk memberikan pemahaman tentang bagaimana orang melihat, memahami, dan merespon suatu situasi dan membantu mengidentifikasi adanya perbedaan pandangan dan penilaian individu. Metode yang digunakan dalam penulisan artikel ini adalah literature review. Penelitian ini diawali dengan mencari referensi berupa artikel-artikel yang berkaitan dengan topik penelitian yang akan dilakukan. Kriteria artikel ilmiah yang digunakan sebagai data berupa artikel ilmiah yang bersumber dari jurnal dengan kemutakhiran 10 tahun terakhir yaitu dari 2012-2022. Hasil analisis 3 artikel jurnal yang membahas persepsi peserta didik terhadap media LKPD. Belum banyak artikel yang menjabarkan terkait persepsi peserta didik terhadap penggunaan media LKPD.